Therapy Dogs' and Handlers' Behavior and Salivary Cortisol During Initial Visits in a Complex Medical Institution: A Pilot Study - Clark, Stephanie D.; Smidt, Jessica M.; Bauer, Brent A. (Frontiers in Veterinary Science, 2020)
Therapy dogs provide health benefits for individuals who suffer from illnesses, such as dementia, depression, loneliness, and aggression. Therapy dogs' impact on human health has been thoroughly studied; however, studies on dog welfare have been limited. Additionally, as dogs have evolved with humans, they have learned to read non-verbal social cues. Dogs can read humans' non-verbal body language and can react to their emotions. However, the body language of dogs is poorly understood and can lead to dog owner-directed aggression. Communication plays a vital role to be a cohesive therapy team. The purpose of this study was to assess perceived stress and cortisol concentrations in therapy dogs and their handlers during the first three visits in a hospital setting. Moreover, the study aimed to investigate whether, while in an overstimulating environment, a therapy dog handler can observe his or her dog's body language and correlate such observations to the dog's stress. Nine therapy dog teams from Mayo Clinic's Caring Canine Program participated in this study. A baseline salivary cortisol was collected from the handler and therapy dog each day of the visits. Once the team arrived, a pre-visit salivary cortisol was collected from the handler and therapy dog and, afterward, a post-visit salivary cortisol. Handlers were also asked to fill out a perceived stress survey on their own stress and that of their therapy dogs'. Behavior was documented by a staff member and the handler. For each visit, the therapy dogs were at the hospital on average 47 min and visited with nine people. There was significant correlation (P = 0.02) between the owner's perceived stress of his or her therapy dog and the dog's salivary cortisol concentrations. The handlers noted medium to high stress, and those dogs had higher cortisol concentrations post-visit. There was no significant difference in salivary cortisol for the handler and therapy dog over the course of the three visits and comparing pre- and post-visit. Overall, the dogs displayed mixed behaviors, with the three most reported being panting, lip licking, and yawning. However, salivary cortisol results suggest that the handlers and therapy dogs maintained their welfare state throughout the visits.